Mapping out the path ahead for corporate criminal procedure law in People´s Republic of China - Hugo Luz dos Santos (Revista Brasileira de Direito Processual Penal)
The tale of procedural fairness is, by now, familiar and well worn. People ́s Republic of China criminal system of justice, which is currently gearing towards the pathway of procedural fairness, has (for the better or for the worse) attracted a wide global gaze. Irrespective of the underlying fairness (or the lack thereof) of the grievances brought forth by a worldwide phalanx of critics, China is steadily toiling towards the path of procedural justice, which is rooted firmly in the Rule of Law. Whilst procedural justice and procedural fairness map seamlessly on to the context of corporate criminal procedure law, there is bevy of critical questions that are in dire need of being consistently addressed nonetheless. One which is whether and to what extent politically- charged tools, which seemingly belie the western-borne concept of separation of powers (as the Supreme People ́s Procuratorate Guiding Cases and, to some degree, Supreme People ́s Court Judicial Interpretations) are amenable to forge the path ahead to meeting the fundamental tenets of due process in corporate criminal procedure law in Mainland China. Against this background, this paper aims to answer two sweeping research questions. Firstly, the degree to which corporate governance (and corporate compliance) subdues (and foremost trumps) corporate criminal liability. Secondly, whether and to what extent SPP Guiding Cases have catalyzed a seismic shift in People ́s Republic of China criminal procedural law. Conversely,one central contention of this paper is that a set of fairness-fraught corollaries can be withdrawn from SPP Guiding Cases with a view to map the path forward to fulfilling the baseline standards of both procedural fairness and procedural justice in People ́s Republic of China corporate criminal procedure law.